Bengal partition stories : an unclosed chapter - Fraser, Bashabi; Sengupta, Sheila (Anthem South Asian studies., 2006)
Through oral histories, interviews and fictional retellings, 'Bengal Partition Stories' unearths and articulates the collective memories of a people traumatised by the brutal division of their homeland.